2017
DOI: 10.1093/bja/aex282
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative goal-directed therapy with uncalibrated pulse contour methods: impact on fluid management and postoperative outcome

Abstract: In addition to the correspondence featured in each issue of BJA please be aware that you can submit online comments on all published articles and also submit online standalone items of correspondence too.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…12 Indeed, it has been hypothesized that the individualization of fluid therapy is effective through timely replenishment of fluid for patients who are fluid responders and avoidance of fluid overload for those who do not. 10 With the guidance of IFM protocol, fluid responders are more likely to received more fluid and non-responders likely to receive less. This may explain why the average volume of fluid was comparable between groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Indeed, it has been hypothesized that the individualization of fluid therapy is effective through timely replenishment of fluid for patients who are fluid responders and avoidance of fluid overload for those who do not. 10 With the guidance of IFM protocol, fluid responders are more likely to received more fluid and non-responders likely to receive less. This may explain why the average volume of fluid was comparable between groups.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Multicentre randomized controlled trials (RCTs) and meta-analyses suggest that IFM is beneficial in decreasing postoperative morbidity, shortening hospital length of stay and saving costs. [6][7][8][9][10][11] Most IFM studies have been conducted in patients undergoing major gastro-intestinal surgery . [10][11][12] A limited number of studies have been done among patients undergoing orthopaedic surgery and have yielded conflicting results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Multicentre randomized controlled trials (RCTs) and meta-analyses suggest that IFM is beneficial in decreasing postoperative morbidity, shortening hospital length of stay and saving costs. [6][7][8][9][10][11] Most IFM studies have been conducted in patients undergoing major gastro-intestinal surgery . [10][11][12] A limited number of studies have been done among 3 patients undergoing orthopaedic surgery and have yielded conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Most IFM studies have been conducted in patients undergoing major gastro-intestinal surgery . [10][11][12] A limited number of studies have been done among 3 patients undergoing orthopaedic surgery and have yielded conflicting results. For instance, in patients undergoing hip fracture surgery, a few studies 13,14 reported clinical benefits when using IFM, whereas others did not.…”
Section: Introductionmentioning
confidence: 99%